ISLAMIC EDUCATION AS AN EFFORT TO STRENGTHEN SOCIAL INTEGRATION IN MULTICULTURAL SOCIETIES - Wala; Herlin Misliani (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2025)
Indonesia as a multicultural country faces complex challenges in maintaining social integration amidst the diversity of ethnicities, religions, and cultures. In this context, Islamic education is expected to play a role as a strategic instrument to bridge differences and strengthen social cohesion. This study aims to examine the role of Islamic education in supporting social integration in a multicultural society, as well as to identify factors that support and hinder the process. Using a qualitative approach with a case study method, data were obtained through in-depth interviews, participant observation, and document analysis from a number of Islamic educational institutions operating in areas with high levels of diversity. The results of the study indicate that Islamic education based on the values ​​of tolerance, inclusiveness, and collaboration is able to increase social awareness and mutual respect among students. The active involvement of parents and the practice of interfaith dialogue in the educational process have also been shown to contribute positively to strengthening social integration. These findings confirm that Islamic education has significant potential in shaping students' characters who are responsive to diversity, while strengthening intergroup relations in society. This study makes an important contribution to the development of educational policies that are more inclusive and adaptive to the dynamics of a multicultural society.